Penerapan Layanan Bimbingan Kelompok untuk Mengembangkan Karakter Alpha girl pada Siswi Sekolah Menengah Atas - Catherine James (Damai : Jurnal Pendidikan Agama Kristen dan Filsafat, 2026)
This study aims to analyze the implementation of group guidance services in developing alpha girl characteristics among senior high school (SMA) female students. The method used is a literature review by examining various relevant sources, including books and scientific journals published within the last five years. The findings indicate that group guidance plays a significant role in shaping alpha girl characteristics through social interaction, group dynamics, communication skills, and participatory learning experiences. Through the stages of formation, transition, core activities, and termination, students gradually experience improvements in self-confidence, independence, leadership ability, and the courage to express themselves in social settings. This developmental process does not occur instantly but emerges through repeated experiences supported by a conducive group environment, effective facilitation from counselors, and continuous self-reflection. In addition, peer feedback within the group contributes to strengthening personal awareness and emotional maturity. Therefore, group guidance services can serve as an effective and systematic strategy in supporting the development of alpha girl characteristics among senior high school female students.